Thursday

April 17, 2014

April 17, 2014

Posted by **Bolu** on Tuesday, October 11, 2011 at 6:19pm.

- math -
**Reiny**, Tuesday, October 11, 2011 at 7:44pmlet's complete the square

2(x^2 + 4x + ....) + 5(y^2 + 2y + ...) = -3

2(x^2 + 4x + 4) + 5(y^2 + 2y + 1) = -3 + 8 + 5

2(x+2)^2 + 5(y+1)^2 = 10

divide by 10

(x+2)^2/5 + (y+1)^2/2 = 1

can you take it from there?

**Related Questions**

math - Which equation shows the correct use of power of products property? a) (...

algebra - Am i doing this right? - 5y^3(y^5)2 _______________ 10y^5(y^2)^6 5y^3...

math - 4x+5y=5 8x+10y=10

Math - Solve the system of linear equations by elimination. Thank You for your ...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

math - Find the ordered pair using the elimination method. 4x+5y=3 8x+10y=6

Algebra - How come when you find the square of the binomial (2x-5y)^2, the ...

math - Find the foci for the equation of an ellipse: 2x^2 + 8x + y^2 + 4 = 0

Algebra 2 - maximize p=6x+10y minimize p=14x+9y use elimination to solve: 4x+5y=...

alegbra - I need help with these problem someone told me that you was not ...